G45R mutation in the nonstructural protein 1 of A/Puerto Rico/8/1934 (H1N1) enhances viral replication independent of dsRNA-binding activity and type I interferon biology. Issue 1 (December 2016) - Kaewborisuth, Challika; Zanin, Mark; Häcker, Hans; Webby, Richard; Lekcharoensuk, Porntippa
Abstract Background The nonstructural protein 1 (NS1) of influenza A viruses can act as a viral replication enhancer by antagonizing type I interferon (IFN) induction and response in infected cells. We previously reported that A/Puerto Rico/8/1934 (H1N1) (PR8) containing the NS1 gene derived from A/swine/IA/15/1930 (H1N1) (IA30) replicated more efficiently than the wild type virus. Here, we identified amino acids in NS1 critical for enhancing viral replication. Methods To identify a key amino acid in NS1 which can increase the virus replication, growth kinetics of PR8 viruses encoding single mutation in NS1 were compared in A549 cells. NS1 mutant functions were studied using dsRNA-protein pull down, RIG-I mediated IFNβ-promoter activity assays and growth curve analysis in murine lung epithelial type I (Let1) cells. Results The G45R mutation in the NS1 of PR8 (G45R/NS1) virus is critical for the enhanced viral replication in A549 cells. G45R/NS1 slightly decreased NS1 binding to dsRNA but did not interfere with its suppression of RIG-I-mediated type I IFN production. Likewise, replication of G45R/NS1 virus was increased in comparison to wild type virus in both wild type and type I interferon receptor null Let1 cells. Conclusions The non-conserved amino acid, R45, enhances viral replication which is apparently independent of dsRNA binding and suppression of type I IFN, suggesting a non-characterized function of NS1 for the enhanced viral replication. As G45R/NS1 virus induced the type I IFN induction and response in infected A549 cells, it is also interesting to investigate virus virulence for further studies.